A Protective Barrier in Dental Clinics: Disposable Mobile Sleeves - Sanchi Gupta; Manisha Lakhanpal Sharma; Vandana Srivastava; Manu Dhillon (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Aim: To evaluate the presence of microorganisms on mobiles phones in dental clinics, as a possible nidus for infection and to suggest the use of disposable sleeves to reduce the level of microorganisms in the dental clinics. Materials and Methods: An observational study was conducted, on two groups, study group (group I) and control group (group II), having 25 mobile phones. Before entering the dental clinics, the mobiles phones were cleaned with an alcohol based disinfectant under aseptic conditions. Then, the mobile phones in group I were covered with an autoclaved disposable sleeve having a chemical indicator and group II were left uncovered. After five hours, swabs were obtained from the surfaces of mobile phones of both group I and group II. The swabs were cultured and incubated on blood agar for twenty four hours and evaluated for their microbial load. Results: The sample taken from the sleeve showed growth of microorganisms whereas, there was no growth on mobile surface of group I. On the contrary, the mobile surface of group II showed significant microbial load. Conclusion: Mobile phones can act as a fomite in dental setup and the use of disposable sleeves can effectively curtail any cross contamination of microorganisms, thereby, serving as a protective barrier. Therefore, these sleeves act as yet another protective barrier in dental clinics. a simple, economical and easily procurable mobile sleeve can make a pertinent difference in the clinics.